2004
DOI: 10.1111/j.1526-4610.2005.05006.x
|View full text |Cite
|
Sign up to set email alerts
|

Low Income and Education Levels May Cause Medication Overuse and Chronicity in Migraine Patients

Abstract: We report that migraineurs with low socioeconomic status may have risk of developing MOH. A better identification of patients at risk of drug-associated headache may contribute to improved health in a group of patients with MOH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
34
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 38 publications
4
34
0
Order By: Relevance
“…Still, the most likely reason is that primary headache disorders in general, and migraine in particular, are more common in women (8), and these are the principal risk factors for MOH since an antecedent headache is a necessary precondition. With regard to gender differences noted in this study, women had significantly lower incomes than men, and lower income has been noted as a risk factor for medication overuse and for headache chronicity (21). While relative poverty of a particular demographic group may affect health across populations, it seems unlikely to do so between genders, at least among those living within families who, presumably, share their income.…”
Section: Discussionmentioning
confidence: 85%
“…Still, the most likely reason is that primary headache disorders in general, and migraine in particular, are more common in women (8), and these are the principal risk factors for MOH since an antecedent headache is a necessary precondition. With regard to gender differences noted in this study, women had significantly lower incomes than men, and lower income has been noted as a risk factor for medication overuse and for headache chronicity (21). While relative poverty of a particular demographic group may affect health across populations, it seems unlikely to do so between genders, at least among those living within families who, presumably, share their income.…”
Section: Discussionmentioning
confidence: 85%
“…As for other frequent headaches, MOH patients tend to be of low socioeconomic status with low income and education, but it is uncertain whether this may be a cause of or an effect of headache 40,42,61,74,75. A high prevalence of smoking, elevated body mass index, and sleeping problems have also been found among MOH patients 42,44.…”
Section: Risk Factors For Mohmentioning
confidence: 99%
“…Neither of these features have been correlated with migraine prevalence and consultation patterns [14,15], whereas they might represent risk factors for medication overuse and chronicity [16]. In this regard, Rasmussen showed that none of the sociodemographic variables: marital status, cohabitation, educational level, occupational category or employment status were significantly associated with migraine [13].…”
Section: Discussionmentioning
confidence: 96%